What's in a Name? The Hidden Historical Ideologies Embedded in the Black and African American Racial Labels. (November 2021) - Hall, Erika V.; Townsend, Sarah S. M.; Carter, James T.
History can inconspicuously repeat itself through words and language. We explored the association between the "Black" and "African American" racial labels and the ideologies of the historical movements within which they gained prominence (Civil Rights and Black Power, respectively). Two content analyses and two preregistered experimental studies ( N = 1, 204 White American adults) show that the associations between "Black" and "bias and discrimination" and between "African American" and "civil rights and equality" are evident in images, op-eds, and perceptions of organizations. Google Images search results for "Black people" evoke more racially victimized imagery than search results for "African American people" (Study 1), and op-eds that use the Black label contain more bias and discrimination content than those that use the African American label (Study 2). Finally, White Americans infer the ideologies of organizations by the racial label within the organization's name (Studies 3 and 4). Consequently, these inferences guide the degree to which Whites support the organization financially.